2009
DOI: 10.1007/s11682-009-9069-0
|View full text |Cite
|
Sign up to set email alerts
|

Association Study between Auditory P3a/P3b Event-Related Potentials and Thought Disorder in Schizophrenia

Abstract: Thought disorder is considered as one of the core features of schizophrenia and several research groups previously reported an association between P300 (P3b) amplitude and thought disorder in schizophrenia. However, previous studies have not evaluated two P300 subcomponents (P3a and P3b) to investigate whether the relationship with thought disorder was specific to P3b. In this study, we measured P3b and thought disorder of 60 patients with schizophrenia. We also measured P3a of 36 patients out of this sample. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…They found significant correlation of P3b ( r = -0.322, p = 0.012) and non-significant correlation of P3a ( r = 0.088, p = 0.609) with a mean peak P3a at Fz of 11.15 μV ± 4.4 μV in controls and 8.75 μV ± 5.7 μV in schizophrenics. Both correlation results are supported by the idea that the frontal lobe activity generates P3a for attention processing while P3b is strongly linked to memory by the measure of CIPTD (Kirihara et al, 2009). Recent work has proposed to systematically study ERP markers after each therapy and use predictive coding in schizophrenia response (Mugruza-Vassallo, 2016).…”
Section: Introductionmentioning
confidence: 53%
See 1 more Smart Citation
“…They found significant correlation of P3b ( r = -0.322, p = 0.012) and non-significant correlation of P3a ( r = 0.088, p = 0.609) with a mean peak P3a at Fz of 11.15 μV ± 4.4 μV in controls and 8.75 μV ± 5.7 μV in schizophrenics. Both correlation results are supported by the idea that the frontal lobe activity generates P3a for attention processing while P3b is strongly linked to memory by the measure of CIPTD (Kirihara et al, 2009). Recent work has proposed to systematically study ERP markers after each therapy and use predictive coding in schizophrenia response (Mugruza-Vassallo, 2016).…”
Section: Introductionmentioning
confidence: 53%
“…H1: Based on previous results regarding P3a amplitude in controls (Gonsalvez et al, 1999; Gonsalvez and Polich, 2002) and in schizophrenic patients (Kirihara et al, 2009), there will be a decrease in amplitude of P3a over time to novel stimuli (that replace the tone cue) as task duration (familiarity) increases, and that this will be greater in the control than in the schizophrenic participants.…”
Section: Introductionmentioning
confidence: 91%
“…Several studies found reduced P3a amplitude in chronic SZ (Devrim-Üçok et al, 2006;Hamilton et al, 2018;Jahshan et al, 2012a;Kirihara et al, 2009;Mathalon et al, 2000;Pfefferbaum et al, 1989;Rissling et al, 2012) as well as in FEP patients (del Re et al, 2015;Hermens et al, 2010;Jahshan et al, 2012a;Kaur et al, 2011;Kruiper et al, 2018;Morales-Muñoz et al, 2017), suggesting that P3a deficit is already present at an early stage. The N1 and P2 ERPs reflect perceptual information registration and processing (Dien et al, 2004;Picton and Hillyard, 1974).…”
Section: Introductionmentioning
confidence: 99%
“…Only a few studies have investigated both the P3b and the P3a components in the same subjects (Kirihara et al, 2009; Mathalon et al, 2010), and to the best of our knowledge not in clinical high risk or recent onset individuals. The aim of the present investigation was thus to assess the P3a and the P3b, in addition to the mid-latency N100 and P200 components, in clinical high risk (HR) subjects, in first episode schizophrenia (FESZ) subjects and in age-matched healthy controls (HC) cross-sectionally, where all subjects including CHR, FESZ and HC were assessed on auditory classical and novelty oddball tasks.…”
Section: Introductionmentioning
confidence: 99%